Role of Quercetin in Modulating Chloride Transport in the Intestine - Yu, Bo; Jiang, Yu; Jin, Lingling; Ma, Tonghui; Yang, Hong (Frontiers in Physiology, 2016)
Epithelial chloride channels provide the pathways for fluid secretion in the intestine. Cystic fibrosis transmembrane conductance regulator (CFTR) and calcium-activated chloride channels (CaCCs) are the main chloride channels in the luminal membrane of enterocytes. These transmembrane proteins play important roles in many physiological processes. In this study, we have identified a flavonoid quercetin as a modulator of CaCC chloride channel activity. Fluorescence quenching assay showed that quercetin activated Clˉ transport in a dose-dependent manner, with EC50 37 µM. Short-circuit current analysis confirmed that quercetin activated CaCC-mediated Clˉ currents in HT-29 cells that can be abolished by CaCCinh-A01. Ex-vivo studies indicated that application of quercetin to mouse ileum and colon on serosal side resulted in activation of CFTR and CaCC-mediated Clˉ currents. Notably, we found that quercetin exhibited inhibitory effect against ANO1 chloride channel activity in ANO1-expressing FRT cells and decreased mouse intestinal motility. Quercetin-stimulated short-circuit currents in mouse ileum was multi-component, which included elevation of Ca2+ concentration through L-type calcium channel and activation of basolateral NKCC, Na+/K+-ATPase and K+ channels. In vivo studies further revealed that quercetin promoted fluid secretion in mouse ileum. The modulatory effect of quercetin on CaCC chloirde channels may therefore represent a potential therapeutic strategy for treating CaCC-related diseases like constipation, secretory diarrhea and hypertension. The inverse effects of quercetin on CaCCs provided evidence that ANO1 and intestinal epithelial CaCCs are different calcium-activated chloride channels.